H.R. 1008 A BILL TO PROTECT THE HEALTH OF NONSMOKERS WORKING AND VISITING IN UNITED STATES GOVERNMENT BUILDINGS FROM THE HAZARDS OF INVOLUNTARY SMOKING - RITTER; SCHEUER (Tufts Archival Research Center, 2007)
Copy of Bill H.R. 1008 which restricts smoking in government buildings to designated areas.